If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -85 = -5(3 + 7r) -85 = (3 * -5 + 7r * -5) -85 = (-15 + -35r) Solving -85 = -15 + -35r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '35r' to each side of the equation. -85 + 35r = -15 + -35r + 35r Combine like terms: -35r + 35r = 0 -85 + 35r = -15 + 0 -85 + 35r = -15 Add '85' to each side of the equation. -85 + 85 + 35r = -15 + 85 Combine like terms: -85 + 85 = 0 0 + 35r = -15 + 85 35r = -15 + 85 Combine like terms: -15 + 85 = 70 35r = 70 Divide each side by '35'. r = 2 Simplifying r = 2
| -3(-6+4r)=90 | | -8(2v+6)=-96 | | 5=-10+a | | 5=10+a | | R+6=25 | | 35-x^7=53+x^3 | | Whatisf(x)whenx=2.4 | | 90x=306 | | 2/3-4=-2 | | 8x-3(x+6)=x+14 | | 293-y=131 | | 75+7x=180 | | 2x+10+5x=3 | | 107+4x+15=180 | | 4x+5=107 | | 7y+7=4+2y | | 8(2x-5)+11x= | | X^2-xy-2y^2=(x+y)(x-2y) | | 5/12/3/16 | | 6x-8y=9x+10y-1z | | -3x/4x=21 | | -4.8/6.6 | | 6=2(w-7)-4w | | 5x+4(2x*10)=1 | | 15ab-4a+5b= | | 6x+7-3x=8x-13 | | 39=0.5(-12n+30) | | 4+3[6x-4(5+2x)]= | | 2x+26=146+2x+172 | | (4x+4y)x(4x-4y)= | | h=-16t^2+110t+6 | | (3z-1)/3 |